Internalizing Character Values in Islamic Religious Education Learning Amidst the Digital Era - Desfita Irmayanti (Masagi: Jurnal Pendidikan Karakter, 2026)
This research aims to formulate a strategic framework for internalizing character values in Islamic Religious Education (IRE) to respond to moral disruptions in the digital era. Utilizing a library research method with a qualitative approach, this study performs a critical synthesis of authoritative literature concerning character education and digital ethics. This study adopts a qualitative approach with a library research design. The data sources consist of reputable national and international journal articles and reference books published within the last ten years (2016–2026). Data collection was conducted through selective documentation techniques, while data analysis employed in-depth content analysis encompassing data reduction, descriptive-analytical interpretation, and source triangulation to ensure credibility and validity. The findings indicate that the challenges of cyber anonymity and moral disengagement necessitate a deconstruction of conventional teaching methods. The novelty of this research lies in the integration of Muraqabah (transcendental awareness) and Tabayyun (ethical verification) as automatic internal filters in virtual interactions. The conclusion emphasizes that effective character internalization must shift from external control toward the reinforcement of self-integrity through virtual Uswah Hasanah and digital parenting synergy. This research contributes a theoretical foundation for developing a "Digital Akhlaq" model that is adaptive to the dynamics of Society 5.0, while serving as a practical guide for IRE educators in maintaining the moral authenticity of students in cyberspace.